2001
DOI: 10.1080/03091900110060776
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic defibrillation with chopping-modulated biphasic waveforms

Abstract: The superiority of different biphasic pulses for transthoracic defibrillation was proven by several studies. These efficient waveforms were implemented in some commercially available defibrillators. Recently we have devised and evaluated a biphasic waveform with a specially balanced ratio of the first-to-second phase voltages and with 5 kHz frequency 1:1 on-off chopping. It used less than half the energy for successful defibrillation in comparison with the 'classic' monophasic damped sinusoidal wave and showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In a nonrandomized clinical study, this PB waveform was found to be more effective in cardioversion of AF or atrial flutter compared with a monophasic waveform 8. The PB waveform is designed to deliver a high peak and average current at low energy levels,9, 10 and it is hypothesized that the waveform can deliver high shock efficacy at low energy levels 7, 11…”
Section: Introductionmentioning
confidence: 99%
“…In a nonrandomized clinical study, this PB waveform was found to be more effective in cardioversion of AF or atrial flutter compared with a monophasic waveform 8. The PB waveform is designed to deliver a high peak and average current at low energy levels,9, 10 and it is hypothesized that the waveform can deliver high shock efficacy at low energy levels 7, 11…”
Section: Introductionmentioning
confidence: 99%